2020
DOI: 10.1126/scitranslmed.aaz7715
|View full text |Cite
|
Sign up to set email alerts
|

MHC class II invariant chain–adjuvanted viral vectored vaccines enhances T cell responses in humans

Abstract: Strategies to enhance the induction of high magnitude T cell responses through vaccination are urgently needed. Major histocompatibility complex (MHC) class II–associated invariant chain (Ii) plays a critical role in antigen presentation, forming MHC class II peptide complexes for the generation of CD4+ T cell responses. Preclinical studies evaluating the fusion of Ii to antigens encoded in vector delivery systems have shown that this strategy may enhance T cell immune responses to the encoded antigen. We now … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
20
0
2

Year Published

2020
2020
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 27 publications
(26 citation statements)
references
References 45 publications
4
20
0
2
Order By: Relevance
“…Lower molecular weight signals are indicative of degradation products. This effect was not observed for E1 without Ii, which suggested that Ii induced an accelerated proteasomal degradation, as also reported by Esposito et al (27).…”
Section: Ii-fusion Enhanced Ubiquitination and Proteasomal Degradationsupporting
confidence: 83%
See 2 more Smart Citations
“…Lower molecular weight signals are indicative of degradation products. This effect was not observed for E1 without Ii, which suggested that Ii induced an accelerated proteasomal degradation, as also reported by Esposito et al (27).…”
Section: Ii-fusion Enhanced Ubiquitination and Proteasomal Degradationsupporting
confidence: 83%
“…The molecular basis of the T cell adjuvant effect of Ii has not been fully clarified yet (43), but one of the suggested mechanisms of action is Ii mediated ubiquitination leading to proteasomal degradation of the linked antigen and thereby enhanced MHC-I presentation (Figure 2C) (27). To investigate if this mechanism could also account for the enhanced CD8 + T-cell responses against the Ii-linked MfPV3 antigens, Ii-E1E2E6E7-and E1E2E6E7transfected cells were cultivated in absence or presence of the proteasome inhibitor MG132.…”
Section: Ii-fusion Enhanced Ubiquitination and Proteasomal Degradationmentioning
confidence: 99%
See 1 more Smart Citation
“…This interpretation is also in line with the finding that the epitope repertoire between HCV genotype 1 and genotype 3 or 4, respectively, display little overlap [145,146]. Thus, current research addresses novel adjuvant formulations such as the use of MHC class II invariant chain-adjuvanted viral vectors, enhancing the peak magnitude, breath, and proliferative capacity of HCV-specific T cells induced by the ChAd3-HCV1b-NS prime/MVA-HCV-1b-NS boost vaccine in healthy volunteers [147]. In addition, the team of Eleanor Barnes further optimized the vaccine strategy to generate pan-genotypic T cell responses to conserved subdominant epitopes [148].…”
Section: Lessons From Vaccine Trialssupporting
confidence: 55%
“…If immunogenicity in this population is found to be muted, whether due to opioid use or previous sub-infectious exposures, the addition and use of novel adjuvants or vaccine platforms to enhance immunogenicity in PWID may be required. For example, the inclusion of MHC class II-associated invariant chain in a viral vectored HCV vaccine broadly enhanced CD4 + and CD8 + T cell responses over the original vaccine in recently conducted human clinical trials [ 156 ].…”
Section: Understanding Vaccine Immunogenicity In Populations Most At Risk For Hcvmentioning
confidence: 99%